A outra ponte do arco-íris: discursos e representações LGBTT nas histórias em quadrinhos de super-heróis norte-americanas - Cruz, Dandara Palankof e (2017)
Superhero stories in comic books are a genre par excellence related to action and adventure – qualities historically linked to male behavior. Therefore, it have always been aimed at boys and men and presented fantasies imbued with the characteristics of the normative standard of masculinity. Among them, the compulsory heterosexuality of their characters and stories. But over the last four decades, people who identified themselves as lesbian, gay, bisexual or transsexual have come to occupy spaces in the public agenda; first, claiming the right to the visibility and free exercise of their sexualities and affectivities; and later, demanding the guarantee of their civil rights. The mass media, which not only reflect society but also helps to shape it, began to show some of these discussions and their results. It was no different in comics and so their stories – including the superheroes genre – began to reflect the larger visibility of the LGBTT portion of society. This research presents an attempt to trace the evolution of these representations and discourses, as well as their impact between comic book readers and in mass culture as a whole. To do so, we use mainly the concept of social representations developed by Serge Moscovici to analyze the reasons for the emergence of such characters and their impact on the public; and Foucault's theories on discourse to think over the conditions that give rise to its enunciation, and its role in power relations existing between the different social strata; as well as the readings of JJ Domingos on the aforementioned author's work, regarding the relationship between sexualities and media discourses. We observed throughout the research that, with the greater visibility of LGBTT individuals in society, more characters appeared with this characteristic, more diversified and fully developed in their characterization; they also gained greater visibility and relevance in their respective universes. However, the gradual increase in the presence of such representations and discourses became a cause of clashes between progressive and conservative readers.